EVALUATION OF THE PRE-SERVICE TEACHERS’ WEB-BASED INSTRUCTION ATTITUDES IN PANDEMIC PERIOD: CYPRUS CASE - Özden, Celalettin; Atasoy, Ramazan; Güneyli, Ahmet; Özdal, Hasan (International Online Journal of Education and Teaching, 2023)
With the pandemic, face-to-face education has been replaced by online education almost all over the world. This new situation in education necessitated the consideration of variables that are different from variables addressed in previous studies. In this context, four new variables were addressed in this study. i) pre-service teachers’ preference between face-to-face education and online education, ii) pre-service teachers’ status of having received online education before the pandemic, iii) attitude levels of pre-service teachers from the same discipline (language education) but in different departments (English or Turkish), and iv) grade levels (students enrolled in the respective undergraduate program after the onset of the pandemic had only online education by the time they moved to second year in the respective program, whereas students of higher grade levels had face-to-face education before the pandemic and online education with the start of the pandemic). This study designed in the quantitative research approach and is based on the descriptive survey model. The research was carried on during the 2020-2021 academic year. With the using aim in the research, data was collected from the pre-service teachers who randomly selected from 12 universities that has Turkish and English language teaching departments. The data were collected using “Web Based Instruction Attitude Scale”. In this research, it was found that the attitudes of the pre-service teachers, who had online education experience, towards web-based learning, were high and their resistance to web-based learning was low. It was revealed that pre-service teachers, who preferred face-to-face education, showed resistance to web-based learning.